2022
DOI: 10.1002/slct.202104617
|View full text |Cite
|
Sign up to set email alerts
|

Mild Synthesis of a Dimethoxy‐Terminated Siloxane through a Ring‐Opening Reaction

Abstract: Alkoxy-terminated siloxanes can be used as coupling agents to improve the properties of materials, and they are also widely used in organic synthesis. Herein, a method to synthesize a dimethoxy-terminated siloxane by the ring-opening reaction of 2,4,6-trimethyl-2,4,6-trivinyl-1,3,5,2,4,6-trioxatrisilinane (D 3 -Vi) and methanol under mild condition was reported. The reaction does not require strong acids, strong bases or transition metal catalysts. The structure of the product was confirmed by 1 H-NMR, 29 Si-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…XRD results showed that the addition of NZSP could inhibit the crystallization and enhance the chain segment movement of PEO, increasing the ionic conductivity. [ 41 ] Thus, the as‐result CSSE exhibited a high ionic conductivity of 3.14 × 10 −4 S cm −1 at 60 °C and achieved a high sodium ion transference number of 0.66. EIS and CV curves were coupled unveiling that the uniform distribution of NZSP in the PEO could improve the interfacial contact and accelerate redox kinetics.…”
Section: Tailoring the Solid Electrolytementioning
confidence: 99%
“…XRD results showed that the addition of NZSP could inhibit the crystallization and enhance the chain segment movement of PEO, increasing the ionic conductivity. [ 41 ] Thus, the as‐result CSSE exhibited a high ionic conductivity of 3.14 × 10 −4 S cm −1 at 60 °C and achieved a high sodium ion transference number of 0.66. EIS and CV curves were coupled unveiling that the uniform distribution of NZSP in the PEO could improve the interfacial contact and accelerate redox kinetics.…”
Section: Tailoring the Solid Electrolytementioning
confidence: 99%